Factors Affecting the Competitive Advantages and Performance of Thai Construction Industry Organizations - Somna, Nuttsuporn (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
This research aims to develop a conceptual framework. Factors Affecting the Competitive Advantages and Performance of Thai Construction Industry Organizations Researchers used the review of research papers and the relationship between variables to confirm the conceptual framework. Research findings. 1) Human resource management, Transformational Leadership and innovation management directly affect the competitive advantage of Thailand’s construction industry 2) Human resource management, Transformational Leadership and innovation management indirectly affect the performance of the construction industry. Competitive advantage will directly affect the performance of Thailand’s construction industry. Article history: Received 8 March 2023 Revised 16 April 2023 Accepted 17 April 2023 SIMILARITY INDEX = 0.89 %